PENGARUH PENGGUNAAN SMARTPHONE TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR DI KECAMATAN MAPANGET KOTA MANADO - Kosmas Sobon; Jelvi M. Mangundap; Stief Walewangko (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2020)
The aim of this research is to explain influence smartphone on learning motivation of students in elementary school, Mapanget Subdistrict, Manado City. This research is in four elementary schools: SD Inpres 03 Paniki Bawah, SD Katolik Santo Yohanes Mapanget Barat, SD Katolik 02 Santo Don Bosco Paniki Bawah; and SD Katolik 10 Santo Fransiskus Buha. Samples those used are 84 students. This research is a quantitative approach. It used the survey’s method. It have stages: observation of the location of the research, preparation of questionnaires, distribution of questionnaires, validity testing, data collection, processing of research results, analysis of the results of research, and discussion. The result showed that the effect of smartphone on the learning motivation of students in elementary school Mapanget Subdistrict was 0.057 or 5.7% with a significance 0.028 < 0,05. The results of testing t-table is greater than t count, namely t-hitung = 2.232 ≥ (t-tab) = 1.989. This means that smartphone have an effect on students’ learning motivation even though it is in the low category 5.7%. Suggestion as recommendation: students do not use excessive smartphones both at school and at home. Parents and teachers always supervise children especially using of smartphone everday because the effect of smartphone on students’ learning motivation is very low.